2020
DOI: 10.18805/ijare.a-5581
|View full text |Cite
|
Sign up to set email alerts
|

Seed Borne Endophytic Fungi Associated with Some Indigenous Rice Varieties of North East India and Their Growth Promotion and Antifungal Potential

Abstract: Background: Seed borne endophytic fungi play an important role in seed germination and plant health. There are ubiquitous and have been found associated in every plant species investigated so far. They colonize plant seeds without causing any disease and are often vertically transmitted. Despite their occurrence, seed borne endophytic fungi are poorly investigated and their role for application in agriculture is still to be elucidated. Methods: In the present study endophytic fungi associated with seeds of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Endophytic fungi were found in rice roots, stems, leaves, and grains through a culture-dependent method, mainly concentrated in more than 60 genera. Penicillium, Aspergillus, and Fusarium are the most common fungi in rice plants [10,[31][32][33]38,40,43,44,48,[50][51][52][53][54][55][56][57], which can be visualized in Figure 2. Herein, we conducted statistical analysis on the percent of identified isolates through a culture-dependent method from the literature and found that they are mainly distributed in five phyla using the Origin 2021 software, namely Ascomycota, Basidiomycota, Mucoromycota, Oomycota, and Zoopagomycota, with Ascomycota being the main group (Figure 3).…”
Section: Variations In Endophytic Fungal Communities In Rice: Explori...mentioning
confidence: 99%
“…Endophytic fungi were found in rice roots, stems, leaves, and grains through a culture-dependent method, mainly concentrated in more than 60 genera. Penicillium, Aspergillus, and Fusarium are the most common fungi in rice plants [10,[31][32][33]38,40,43,44,48,[50][51][52][53][54][55][56][57], which can be visualized in Figure 2. Herein, we conducted statistical analysis on the percent of identified isolates through a culture-dependent method from the literature and found that they are mainly distributed in five phyla using the Origin 2021 software, namely Ascomycota, Basidiomycota, Mucoromycota, Oomycota, and Zoopagomycota, with Ascomycota being the main group (Figure 3).…”
Section: Variations In Endophytic Fungal Communities In Rice: Explori...mentioning
confidence: 99%
“…Seed microbiomes differ from one plant to another due to the quality of the seeds, viability, cultivars and energy reserves needed for microbial metabolism (Roy et al, 2021 ). The host, microorganisms and environment are the major factors influencing microbial compositions in the plant‐seed endosphere (Figure 1 ).…”
Section: Which Factors Determine the Composition Of Seed Microbiomes?mentioning
confidence: 99%
“…Ariyanto et al (2013) found ten endophytic fungi in rice using Integrated Pest Management (IPM) system, namely Aspergillus, Penicillium, Nigrospora, Trichoderma, Alternaria, Curvularia, Fusarium, Mucor, Mastigosporium, and Monosporium, whereas in rice plants with conventional cropping systems found seven endophytic fungi Aspergillus, Nigrospora, Curvularia, Trichoderma, Penicillium, Verticillium, and Acremonium. The diversity of endophytic fungi in rice plants is also influenced by different varieties (Roy et al 2020). The morphological characteristics of each entomopathogenic rice endophytic fungus are described as follows:…”
Section: Entomopathogenic Endophytic Fungimentioning
confidence: 99%